Kajian pelu dan tidaknya penambahan term Budi Pekerti dalam konten buku Pendidikan Agama Islam dan Budi Pekerti untuk siswa SMU - Ashar, Salim (Sekolah Tinggi Ilmu Tarbiyah Raden Wijaya Mojokerto, 2017)
Character is a complicated issue, even considered an abstract problem. It is said to be abstract because the concept of manners is not yet operational. While good and bad standards for morals are in the objective view of God the Creator of man. If the character is ethics, it is very dangerous, because some of its value will be contrary to the moral lessons that exist in religious subjects. When both are taught (ethics and morals) then the threat is the students will later experience what is called a split personality, that is split personality. Students become confused because there are conflicting values, such as good values ​​in the sense of morals and good value in manners (call: ethics). There is no honest terminology of Arabic versions, honest English versions, false witnesses of Arabic and French versions, as there is no terminology about Arab or Turkish morality. This applies to humans when there is a pattern of intersection between ethical values ​​and customs: ethical values ​​derive from the